Liberdade e Capital em Karl Marx - Prado, Carlos Batista (2010)
The main objective of this dissertation is to analyze the issues surrounding liberty from The Capital by Karl Marx. This study aims to understand how the philosophical issue of liberty is challenged by exposition dialectic of The Capital . With reference to the interpretation of Benoit, understand that the exposition method of The Capital can only be understood in light of the philosophy of Hegel and the dialectical tradition. The exposition moves from abstract to concrete. The concepts presented are developed from their simplest form and apparent, and continue advancing through a negative movement to more complex forms and concrete. The exposition route developed in The Capital is a path of ascent, which is part of abstract shapes to overcome them, deny them and reach the reality which hides behind the mystifying ways, unveiling the myths of bourgeois society and bringing to the surface the contradictions immanent in capital. This exposition is the dialectic methodological tool that enables Marx to try to overcome the form merely analytical and empirical research, reconstructing the totality of the tangible real and alive, from the negative force of dialectics. Marx build a unity between the logical and history form of representation, a synchronic and diachronic structure, a contradictory unity between being and becoming. A unit that includes a concrete representation of reality, able to overcome the abstract forms by the motion of denial from an adversarial logos. The exposition seeks to unveil the dialectical contradictions within each category of capitalist society. The negative movement of the exposition puts the categories on the move, becoming permanent. The categories are transformed, are denied and yet still preserve a truth value. This means that categories put to negative dialectics of exposition, and may be non-being at the same time and in the same relation. Based on these principles, this research develops the thesis that the concept of liberty in The Capital Marx's theory is thought of as a positive-negative liberty. The exposition method reveals that under the capitalist mode of production liberty is contradictory, the man appears as free and non-free at the same time. In a society dominated by capital, Marx speaks of liberty and unliberty. The positivity liberty in capital is revealed by analyzing the market and the movement of goods that require relationship between men formally free and equal. Moreover, the negativity liberty is expressed in the capital area under the relations of production, fetishism, the autocracy of capital under Labour. Liberty and unliberty coexist in capitalist relations, appears as a prerequisite for another. Marx shows that the process of capitalist exploitation is mediated by the principles of liberty which govern and regulate the market. That means it is Liberty itself that appears as a legal prerequisite for unliberty and domain of capital under men.